2016
DOI: 10.1144/pgc8.20
|View full text |Cite
|
Sign up to set email alerts
|

The Lancaster Field: progress in opening the UK's fractured basement play

Abstract: To date, fractured crystalline basement reservoirs (basement) on the UK Continental Shelf (UKCS) have largely been underexplored, despite the fact that numerous indications of hydrocarbons have been reported from basement in wells dating back to the 1970s. As production from the UKCS continues to decline, and with the exploration potential of more traditional plays becoming increasingly mature, the potential of the overlooked and underrated basement play warrants further exploration. Over the last 10 years, Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…The unaltered condition of the basement cores suggests that the Rona Ridge is little affected by deep subaerial weathering. However, analysis of seismic reflection data and cores from the Lancaster Field (Slightam, 2012;Belaidi et al, 2018) has revealed the presence of mineralized sediment-filled and breccia-filled fissures, several hundred meters deep, and up to several meters wide. These findings are consistent with the sediment-and mineral-filled fracture systems reported here all along the Rona Ridge at depths many hundreds of meters below local top basement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unaltered condition of the basement cores suggests that the Rona Ridge is little affected by deep subaerial weathering. However, analysis of seismic reflection data and cores from the Lancaster Field (Slightam, 2012;Belaidi et al, 2018) has revealed the presence of mineralized sediment-filled and breccia-filled fissures, several hundred meters deep, and up to several meters wide. These findings are consistent with the sediment-and mineral-filled fracture systems reported here all along the Rona Ridge at depths many hundreds of meters below local top basement.…”
Section: Discussionmentioning
confidence: 99%
“…1B; Coney et al 1993). Other assets, such as the Lancaster Field and associated discoveries in the southwest Rona Ridge, are hosted almost entirely within fractured basement (Trice, 2014;Belaidi et al, 2018; >18 billion barrels of oil initially in place). CITATION: Holdsworth, R.E., et al, 2019, Natural fracture propping and earthquake-induced oil migration in fractured basement reservoirs: Geology, v. 47, p. 1-5, https:// doi .org /10 .1130 /G46280.1 Geochemical studies of oils suggest a Late Jurassic Kimmeridge Clay source rock (Holmes et al, 1999;Finlay et al, 2011), thought to occur on the downfaulted flank of the ridge in the Faroe-Shetland Basin to the northwest (Ritchie et al, 2011).…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations reported here were made at wells drilled as part of a fractured basement exploration (Trice, 2014) of the Lancaster field, west of Shetland in the North East Atlantic (Figure 1). The Lancaster field is now undergoing development (Belaidi et al, 2018). The protective structure was in an area where the majority of the seabed consists of coarse sandy sediment with areas of hard substratum (boulders) to the north and west (Figure 2).…”
Section: Study Area and Drilling Historymentioning
confidence: 99%
“…Despite the improved porosity associated with fault zones, mapping of porosity using seismic methods is not possible, and areas of potential high porosity are quantified through the mapping of seismic-scale faults and attributing fault zone widths as statistical ranges. Fault zone widths are estimated from the ranges of fault zones established through drilling and wireline data (Belaidi et al 2016). Porosity generation is attributed to a pre-existing fracture network that has been enhanced by a combination of fissuring (tensile failure), partial mineralization due to influx of hydrothermal fluids (e.g.…”
Section: Effective Porosity and Permeability Developmentmentioning
confidence: 99%